2004
DOI: 10.1123/ijsnem.14.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Discomfort during Intermittent High-Intensity Exercise: Effect of Carbohydrate–Electrolyte Beverage

Abstract: This study investigated whether different beverage carbohydrate concentration and osmolality would provoke gastrointestinal (GI) discomfort during intermittent, high-intensity exercise. Thirty-six adult and adolescent athletes were tested on separate days in a double-blind, randomized trial of 6 % and 8 % carbohydrate-electrolytes (CHO-E) beverages during four 12-min quarters (Q) of circuit training that included intermittent sprints, lateral hops, shuttle runs, and vertical jumps. GI discomfort and fatigue su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 39 publications
0
25
0
2
Order By: Relevance
“…Estes são divididos em sintomas superiores (vômitos, náuseas e pirose retroesternal -azia) e inferiores (diarréia, cólica abdominal, perda de apetite, sangramento, aceleração dos movimentos intestinais e vontade de defecar) (6,(12)(13)(14)(15)(16)(17) . A etiologia dos sintomas gastrintestinais durante o exercício é multifatorial e inclui a redução do fluxo sanguíneo intestinal, a liberação de hormônios gastrintestinais (11,(18)(19)(20)(21)(22)(23)(24) , o estresse mecânico sobre o TGI (25,26) , a desidratação (27)(28)(29) , os fatores psicológicos (30) , a idade (31,32) , o sexo (13,22,31,32) , a dieta (22,23,33,34) e o nível de treinamento do indivíduo (23) . Comentaremos a seguir as principais causas para o desenvolvimento de sintomas gastrintestinais em praticantes de exercícios de longa duração.…”
Section: Efeitos Maléficos Do Exercício Sobre O Tgiunclassified
See 1 more Smart Citation
“…Estes são divididos em sintomas superiores (vômitos, náuseas e pirose retroesternal -azia) e inferiores (diarréia, cólica abdominal, perda de apetite, sangramento, aceleração dos movimentos intestinais e vontade de defecar) (6,(12)(13)(14)(15)(16)(17) . A etiologia dos sintomas gastrintestinais durante o exercício é multifatorial e inclui a redução do fluxo sanguíneo intestinal, a liberação de hormônios gastrintestinais (11,(18)(19)(20)(21)(22)(23)(24) , o estresse mecânico sobre o TGI (25,26) , a desidratação (27)(28)(29) , os fatores psicológicos (30) , a idade (31,32) , o sexo (13,22,31,32) , a dieta (22,23,33,34) e o nível de treinamento do indivíduo (23) . Comentaremos a seguir as principais causas para o desenvolvimento de sintomas gastrintestinais em praticantes de exercícios de longa duração.…”
Section: Efeitos Maléficos Do Exercício Sobre O Tgiunclassified
“…Quanto à dieta, a ingestão de altas quantidades de suco de laranja, comidas gordurosas, proteína, vitamina C, bebidas hipertônicas de carboidratos, alimentos ricos em fibras e grandes refeições antes de competição predispõem à manifestação de sintomas gastrintestinais (22,23,33) . Muito embora existam relatos que o consumo de cafeína antes do exercício possa aumentar a queixa de sintomas gastrintestinais, Van Nieuwenhoven et al (34) recentemente mostraram que as queixas dos sintomas gastrintestinais foram maiores em atletas que consumiram solução de carboidratos durante o exercício em comparação com a ingestão de água.…”
Section: Outras Causasunclassified
“…10 From these reviews, it seems that reduced blood flow to the intestine during exercise may be one of the more likely pathophysiological mechanisms for the development of GI symptoms during exercise. 9,10 Although studies have shown that significant physiological changes in splanchnic blood flow occur in response to an acute exercise bout, [11][12][13][14][15][16][17][18][19] there are, to our knowledge, no studies that (1) have investigated the effects of prolonged endurance exercise on splanchnic hemodynamics and (2) specifically linked the development of GI symptoms during prolonged endurance exercise to alterations in splanchnic hemodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulating CHO exo intake could be achieved by ingesting different volumes of a 6% solution; however, ingesting larger volumes may lead to gastrointestinal distress (Shi et al 2004). Furthermore, this practice would not translate well to actual field-based team games, where there are limited opportunities to drink during matches (Clarke et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this practice would not translate well to actual field-based team games, where there are limited opportunities to drink during matches (Clarke et al 2008). Manipulating the [CHO] of the ingested solution may also increase the risk of gastrointestinal distress (Shi et al 2004), but the minimal understanding of CHO tolerance during team games in adolescents, along with the absence of any CHO intake guidelines, provides a rationale for using different [CHO].…”
Section: Introductionmentioning
confidence: 99%